Trenazherno-izmeritel'nyi kompleks dlya opredeleniya skorostno-silovykh parametrov v sportivnoi deyatel'nosti - Pushkarev, E. D.; Dyatlov, D. A.; Kulikov, L. M.; Rukavishnikov, B. M.; Ryzhov, V. I.; Belousov, V. G. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
A simulative metrical complex for speed and power parameters measurement in sport developed in the Scientific Institute Chelyabinsk is presented.